Achieving Sustainability in Manufacturing Micro, Small and Medium Enterprises (MSMEs’) in Tanzania Through Adoption of Solar Energy: Solar energy adoption by manufacturing MSMEs in Tanzania - Felichesmi Lyakurwa (Industrial Engineering Department, Faculty of Science and Engineering, UIN Sunan Kalijaga Yogyakarta, 2022)
Globally, energy demand has increased significantly whereby consumption of nonrenewable energy is dominant. The reliance on nonrenewable energy sources, not only threatens the efforts to achieve the stated Sustainable Development Goals but also affects community’s participation in the economic activities. The increased concern over resource depletion, and environmental impacts, has suggested future reliance on renewable energy. Tanzania has high levels of solar energy, whose exploitation could contribute significantly to energy access. Despite the benefits of renewable energy use, studies to establish factors for energy choice by manufacturing Micro Small and Medium Enterprises (MSME’s) in Tanzania are inadequate. Hence, this study intended to establish the dominant factors for the choice of solar energy by manufacturing industries, and workers perceptions about sustainable manufacturing practices. A cross sectional survey research design was employed whereas questionnaires were used to collect data (n = 236) from employees working in the manufacturing MSMEs’ in the selected districts in Morogoro region. A descriptive, Confirmatory Factor Analysis (CFA) and a multinomial probit (MNP) model were employed to establish the dominant factors for the solar energy use. The MNP results (tested at: 95% confidence level) indicated that not expensive energy source (Pvalue = 0.01) and other factors, including availability of solar appliances (Pvalue = 0.02) have significant influence on industry’s choice of solar energy, while choice of hydro-electricity was significantly influenced by not expensive (Pvalue = 0.01) and advised to use energy source (Pvalue = 0.001). Easy access (Pvalue = 006), and not expensive energy source (Pvalue = 0.001) were found to have significant influence on the use of fossil fuels. Also, the CFA results indicated that all factors i.e., environmental, social, and economic have significant influence on the workers perception about sustainable manufacturing practices. The results therefore, provides critical information to policy making institutions in Tanzania to make informed decisions on the formulation of national strategies that attracts use of renewable energy for manufacturing sustainability.